In the Search of Viral Suppressors of Prunus Infecting Viruses - Fákó, Vivien; Jaksa-Czotter, Nikoletta; Várallyay, Éva (GEORGIKON FOR AGRICULTURE, 2024)
Perennial woody plants can be infected by a wide range of viruses and viroids. During infection, the plant's defence system, the RNA interference (RNAi), the highly effective and specific defence reaction of the host, is induced. Throughout their evolution, viruses have developed strategies to block this defence process in various ways. One of these strategies involves the encoding of proteins that function as viral suppressors of RNA interference (VSR). In our study, we examined the potential RNAi silencing suppressor activity of P21 proteins of little cherry virus-1 (LChV-1) from different host plants (cherry and apricot) and of P4 of peach-associated luteovirus (PaLV). Our results revealed that the P21 protein of LChV-1apricot strain displayed systemic VSR activity, whereas the P4 protein of PaLV showed only weak local suppressor activity.
Keywords: Velarivirus; Luteovirus; LChV-1; PaLV; viral suppressor; agroinfiltration